Harmonic Distortion Analysis Of On-grid Photovoltaic Panel Integration In Load Sharing Scheme - Santoso, Satria Adji; Ulinuha, Agus (Faculty of Engineering, Universitas Tanjungpura, 2025)
Harmonic analysis is crucial to maintain the system power quality, especially in photovoltaic panels with load sharing scheme. Previous studies have discussed the impact of harmonic distortion on electric power systems in general, but there is still limited discussion on on-grid photovoltaic panel systems without the load-sharing scheme. Harmonic is a distortion phenomenon of current and voltage that is higher than fundamental frequency. The consumption of nonlinear loads contributes to the rising of harmonic distortion that has a bad impact on the system's power quality. This study aims to analyze and compare the levels of harmonic distortion on on-grid photovoltaic panels with a load-sharing scheme and evaluate the suitability with the IEEE 519-2014 standard. The result of this study shows that the Total Harmonic Distortion (THD) on the current (THDi) in PLN